QUALITY OF LIFE ASSESSMENT IN MULTIPLE MYELOMA PATIENTS UNDERGOING DOSE-REDUCED TANDEM AUTOLOGOUS STEM CELL TRANSPLANTATION - Alhossain A. Khalafallah; Kristina McDonnell; Hizb U. Dawar; Iain Robertson; David Woods (Mediterranean Journal of Hematology and Infectious Diseases)
Few studies exist that consider health-related quality of life (HR-QOL) in patients with multiple myeloma (MM) undergoing tandem autologous stem cell transplantation (TASCT). Eighteen patients with advanced MM who underwent dose-modified TASCT were enrolled in this study between March 2006 and March 2008. Patients <60 year old (10) received conditioning with melphalan 140 mg/m2 and patients who were ≥60 years (8) received 100 mg/m2. The median age was 57.5 years (range 35-69). We conducted the European Organization of Research and Treatment of Cancer (EORTC) QLQ-C30 questionnaire via interviews at presentation, after each ASCT and thereafter every 3 months for 24 months. Mean global health measure improved from 3.44 before transplant to 4.50 (1=very poor, 7=excellent) at the second and subsequent follow-up visits (P<0.001) and the mean global quality of life score improved from 3.61 to 4.71 (P<0.001). Pain symptom was reduced (P=0.001), and physical functioning improved (P<0.001) throughout the period of post-transplant follow-up. Our study showed that dose-reduced TASCT is well tolerated with low toxicity albeit the transient reduction in QOL during both transplants. Post-transplant follow-up showed significant improvement in overall HR-QOL that reflects positively in the overall disease-outcome.    The EORTC-QLQ-C30 is a practical tool in measuring QOL in myeloma patients.